Synthesis and characterization of aniline-dimer-based electroactive benzoxazine and its polymer. Issue 88 (8th December 2017) - Li, Shuliang; Zhao, Chunxia; Gou, Haolan; Li, Hui; Li, Yuntao; Xiang, Dong
Abstract : Benzoxazine incorporating an aniline dimer in its structure has satisfactory electroactivity and undergoes both amine-catalyzed and autocatalytic polymerization. Abstract : An electroactive aniline-dimer-based benzoxazine (BA–PADPA) was prepared from bisphenol A, p -aminodiphenylamine (PADPA), and paraformaldehyde. The structure of BA–PADPA was successfully confirmed by fourier transform infrared spectroscopy, and 1 H-NMR and 13 C-NMR spectroscopy. Further, BA–PADPA was polymerized into polybenzoxazine by thermal curing. During the thermally induced polymerization, the imino group of PADPA segment first catalyzed the ring-opening reaction of benzoxazine groups of BA–PADPA at about 161 °C. Subsequently, the autocatalytic benzoxazine polymerization process followed at higher temperatures. Both the curing stages of BA–PADPA were completed at lower temperature ranges than those of the bisphenol A/aniline-based benzoxazine (BA–AN). The activation energies for the amine-catalyzed ring-opening and the autocatalytic benzoxazine polymerization were determined by both the Kissinger's and Ozawa's methods. Furthermore, the redox behavior of the as-synthesized BA–PADPA polymer (PBA–PADPA) was evaluated by cyclic voltammetry. The results indicated that the PBA–PADPA coating exhibited a satisfactory corrosion resistance ability with a corrosion rate of 0.0108 mm per year for carbon steel Q235, which is significantly lower than that of the BA–AN polymer coating (PBA–AN). Insights were gained into the anticorrosion mechanism, which indicated that the redox catalytic property of the PADPA segments in PBA–PADPA was probably capable of inducing the formation of a metal oxide layer composed of Fe2 O3 on the steel surface, which was characterized by scanning electron microscopy and X-ray photoelectron spectroscopy. This study provides in-depth investigations and comprehensive understanding of the polymerization behavior of the benzoxazine/aniline-dimer-based system, which are necessary for the design, manufacture, and utilization of this type of high-performance polymeric coating.